The trial of Mrs. Rhinelander [large type] - Bryce, Denny S. (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"New York, 1924. Born to English immigrants who've built a comfortable life, idealistic Alice Jones longs for the kind of true love her mother and father have. She believes she's found it with Leonard "Kip" Rhinelander, the shy heir to his prominent white family's real estate fortune. Alice too, is "white", though she is vaguely aware of rumors that question her ancestry -- gossip her parents dismiss. But when the lovers secretly wed, Kip's parents threaten his inheritance unless he annuls the marriage. Devastated but determined, Alice faces overwhelming odds both legally and in the merciless court of public opinion. But there is one person who can either help her -- or shatter her hopes for good: In the 1940s, her estranged niece, Roberta Brooks, must put aside her disdain for her infamous aunt to combat an unexpected new Rhinelander legal assault. And in the 1920s, reporter Marvel Cunningham lives to chronicle the social change and the Harlem Renaissance's fiery creativity, but when Alice's story dominates the headlines, Marvel's job is to cover it. At first, Marvel and Roberta, in different decades, see Alice's legal entanglements as tabloid sensations generated by a self-hating woman who failed to 'pass'. But the deeper they investigate, the more they will learn about the reasons behind Alice Jones's behavior and what the three women have in common." --